2017
DOI: 10.3390/rs9070647
|View full text |Cite
|
Sign up to set email alerts
|

Poppy Crop Height and Capsule Volume Estimation from a Single UAS Flight

Abstract: Abstract:The objective of this study was to estimate poppy plant height and capsule volume with remote sensing using an Unmanned Aircraft System (UAS). Data were obtained from field measurements and UAS flights over two poppy crops at Cambridge and Cressy in Tasmania. Imagery acquired from the UAS was used to produce dense point clouds using structure from motion (SfM) and multi-view stereopsis (MVS) techniques. Dense point clouds were used to generate a digital surface model (DSM) and orthophoto mosaic. An RG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…The results of the present study support the finding of other studies that high resolution multi-temporal crop height information is needed for successful estimation of crop biomass [10,41]. Alternative plant phenotypic traits, such as plant volume, may even yield more accurate predictors for biomass [40]. Thus, future studies should evaluate the further potential of 3D point cloud analysis for estimating key plant phenotypic traits, which can be used as reliable predictors for plant biomass.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the present study support the finding of other studies that high resolution multi-temporal crop height information is needed for successful estimation of crop biomass [10,41]. Alternative plant phenotypic traits, such as plant volume, may even yield more accurate predictors for biomass [40]. Thus, future studies should evaluate the further potential of 3D point cloud analysis for estimating key plant phenotypic traits, which can be used as reliable predictors for plant biomass.…”
Section: Discussionsupporting
confidence: 88%
“…Crop height is considered as an important indicator for biomass of crops, such as maize [35], barley [12], sorghum [1], and poppy [40]. The predicted vegetable crop height values of the present study show strong and highly significant relationships to the biomass for all three crops ( Figure 5).…”
Section: Discussionmentioning
confidence: 49%
“…Comparatively, the coefficient of correlation increased when the experiment was conducted at later stage, e.g., Varela et al [45] achieved an R 2 of 0.79 in the abovementioned experiment, but used images taken at flowering stage, which denotes a positive relationship between both variables. Similarly, Iqbal et al [9] achieved a stronger correlation (R 2 > 0.9) working in the late season with a broad range of poppy crop heights (0.5-0.9 m), and Bendig et al [7] reported higher deviations from the regression line for younger plants. Therefore, the correlations obtained in this paper are considered very satisfactory, since the experiments were carried out in the challenging very early crop growth stage.…”
Section: Obia-based Crop Height Estimationsmentioning
confidence: 99%
“…Table 2) is comparable to the RMSE of derived plant height based on UAV or LiDAR measurements for other plants (e.g., 3.5 cm for LiDAR measurements on wheat [17], 10-13 cm for UAV-derived plant heights on poppy [18], and 10 cm for winter barley and wheat in [27]) and consistent with the measurements based on the 2014 field experiment presented in [16]. The RMSE of the calibration of the CSM-derived plant height vs. dry biomass regression is consistent if slightly higher when compared to the values achieved in [17] (112 g/m 2 for LiDAR derived plant heights, and 115 g/m 2 for SfM-derived plant heights).…”
Section: Discussionmentioning
confidence: 51%
“…The use of plant height as a predictor for deriving crop biomass is well-established, both for UAV-and LiDAR-based data acquisition [2,[17][18][19] as well as with in-situ measurements [20]. In this study, the CSM-derived plant heights, generated from the oblique stereo RGB imagery, are investigated to validate the potential and the robustness of the newly introduced 3D monitoring system to estimate biomass during plant growth.…”
Section: Introductionmentioning
confidence: 99%